Scandal : The Sexual Politics of the British Constitution - Clark, Anna (Book collections on Project MUSE., 2014)
Are sex scandals simply trivial distractions from serious issues or can they help democratize politics? In 1820, George IV's "royal gambols" with his mistresses endangered the Old Oak of the constitution. When he tried to divorce Queen Caroline for adultery, the resulting scandal enabled activists to overcome state censorship and revitalize reform. Looking at six major British scandals between 1763 and 1820, this book demonstrates that scandals brought people into politics because they evoked familiar stories of sex and betrayal. In vibrant prose woven with character sketches and illustrations, Anna Clark explains that activists used these stories to illustrate constitutional issues concerning the Crown, Parliament, and public opinion.